PENYUSUNAN MICRO MODUL BERBASIS PROBLEM-BASED LEARNING (PBL) BAGI GURU SMK NEGERI 3 JENEPONTO - M. Ridwan Tikollah; SYAHIR FADLI; Nurul Chalisa Majiding; Fajriani Azis; Sahade Sahade (Fakultas Ekonomi dan Bisnis Islam, 2025)
This community service program strengthened vocational teachers’ pedagogical and digital competencies in designing Problem-Based Learning (PBL) micro modules aligned with Indonesia’s Merdeka Curriculum. Using a community-based training approach (preparation and needs assessment, concept reinforcement, and hands-on workshops), a team from Universitas Negeri Makassar facilitated training for X teachers at SMK Negeri 3 Jeneponto. Data were collected through observations, informal interviews, and participants’ reflective notes, and were analyzed descriptively to capture competency changes and implementation constraints. Results indicate that participants improved their understanding of micro module structure and key PBL principles, enhanced their ability to formulate authentic, contextual problem scenarios, and increased confidence in using Canva and other digital tools to develop visually engaging teaching materials. As tangible outputs, teachers produced initial drafts of subject-specific PBL micro modules that are ready for refinement and classroom implementation. Persistent challenges included uneven teacher digital literacy and limited student access to digital devices, leading to a practical need for hybrid delivery and printed micro module versions. These findings imply that future programs should incorporate differentiated digital support, provide low-tech design alternatives, and strengthen school–university collaboration to ensure sustainable implementation of innovative learning materials under the Merdeka Curriculum.